Maintenance of syntenic groups between Cathartidae and Gallus gallus indicates symplesiomorphic karyotypes in new world vultures - Tagliarini, Marcella M. (Sociedade Brasileira de Genética, 2011)
Similarities between New World and Old World vultures have been interpreted to reflect a close relationship and to suggest the inclusion of both in Accipitridae (Falconiformes). However, deeper analyses indicated that the placement of the New World vultures (cathartids) in this Order is uncertain. Chromosome analysis has shown that cathartids retained a karyotype similar to the putative avian ancestor. In order to verify the occurrence of intrachromosomal rearrangements in cathartids, we hybridized whole chromosome probes of two species (Gallus gallus and Leucopternis albicollis) onto metaphases of Cathartes aura. The results showed that not only were the syntenic groups conserved between Gallus and C. aura, but probably also the general gene order, suggesting that New World vultures share chromosomal symplesiomorphies with most bird lineages.